2019
DOI: 10.4067/s0718-27242019000400041
|View full text |Cite
|
Sign up to set email alerts
|

El papel de la Cooperación para Desarrollar Innovación Tecnológica en la PYME

Abstract: La innovación se ha consolidado como una vía para mejorar el desempeño de las economías. El objetivo del estudio es analizar el rol de las cooperaciones y los efectos en la innovación tecnológica y el desempeño de las empresas aplicando PLS-SEM. Para probar el modelo se utilizó la décima encuesta de innovación del Ministerio de Economía de Chile, levantada durante el año 2017. Los resultados muestran que la cooperación comercial y cooperación profesional tienen efecto en la innovación tecnológica, sin embargo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
0
3
0
1
Order By: Relevance
“…In general, it is determined that cooperation with business organizations such as suppliers, buyers, consultants, and other competing companies directly favors business innovation processes. Also, it has been observed that business innovation is facilitated with the collaboration of support organizations such as technology centers, universities, public agencies, and trade associations, which are favored (Etzkowitz & Leydesdorff, 2000;Gallaud, 2013;Cantù et al, 2015b;Marasco et al, 2018;Fuentes et al, 2019;Castillo-Vergara & Torres, 2019). Considering the previous antecedents, and the exploratory nature of this study of firms in the tourism sector in Chile, the following hypotheses are proposed (Figure 1…”
Section: Types Of Innovationmentioning
confidence: 92%
See 1 more Smart Citation
“…In general, it is determined that cooperation with business organizations such as suppliers, buyers, consultants, and other competing companies directly favors business innovation processes. Also, it has been observed that business innovation is facilitated with the collaboration of support organizations such as technology centers, universities, public agencies, and trade associations, which are favored (Etzkowitz & Leydesdorff, 2000;Gallaud, 2013;Cantù et al, 2015b;Marasco et al, 2018;Fuentes et al, 2019;Castillo-Vergara & Torres, 2019). Considering the previous antecedents, and the exploratory nature of this study of firms in the tourism sector in Chile, the following hypotheses are proposed (Figure 1…”
Section: Types Of Innovationmentioning
confidence: 92%
“…Also, it is observed that collabora-tion with support institutions such as public agencies, universities, and technology centers facilitates indirect firm innovation through support instruments and programs (Etzkowitz & Leydesdorff, 2000;Gallaud, 2013;Marasco et al, 2018;Fuentes et al, 2019). For example, Castillo-Vergara & Torres (2019) indicate that business cooperation and professional cooperation affect technological innovation. However, academic collaboration has not a significant effect.…”
Section: Collaborative Innovationmentioning
confidence: 99%
“…Despite the growing research on technological innovation, it has been shown that there is a gap in the literature, however, to promote innovation within companies, specific knowledge is required that is part of the innovation process, which includes the Exchange information, problem solving and learning with other people or organizations. The study of Castillo y Torres in 2019 focused on analyzing the set of written relationships that influence innovation within SMEs, which are identified as academic cooperation, commercial cooperation and professional cooperation, whose objective within the study was to evaluate innovation through an instrument that was used by the Ministry on economy for the year 2017 (Castillo & Torres, 2019).…”
Section: State Of Art Reviewmentioning
confidence: 99%
“…La mayoría de estudios que aborda esta relación, se han centrado en la innovación tecnológica. Estos estudios han encontrado un efecto positivo de la relación con clientes y proveedores sobre la innovación de producto (Miotti & Sachwald, 2003;Nieto & Santamaría, 2007;Castillo-Vergara & Torres-Aranibar, 2019), debido a que la cooperación con estos socios: proporciona conocimiento sobre tecnología y mercados (Whitley, 2002), reduce el tiempo de comercialización y favorece tanto las innovaciones de producto como de proceso (Miotti & Sachwald, 2003;Nieto & Santamaría, 2007).…”
Section: Efectos De Los Tipos De Cooperación Sobre La Innovación Tecnológica Y No Tecnológicaunclassified